A model and algorithm for interconnecting two WANs - Liang, S.-C.; Yee, J.R. (IEEE International Conference on Systems, Man and Cybernetics, 1990, 1990)
The authors consider the problem of determining which gateways to use to interconnect existing wide area networks (WANs) to minimize a linear combination of the average internet and intranet packet delays subject to a cost constraint on the amount to be spent to establish the gateways. This problem is formulated as a nonlinear combinational optimization problem. When the gateway locations are fixed, the resulting routing problem is not a convex programming problem. An algorithm to solve this problem is developed, and computational experience is reported. For light intranet traffic, the algorithm computed solutions that were within 6% of an optimal solution. For medium intranet traffic, the algorithm did not perform as well (error ranging from 5.7% to 16%). In addition, the CPU time used was higher for medium intranet traffic than for light intranet traffic.< >